2021
DOI: 10.21503/hamu.v7i3.2202
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de las características de la Realidad Aumentada aplicada a la educación

Abstract: El avance de las tecnologías de información y comunicación y la incorporación de tecnologías emergentes en la educación, ha dado lugar a al desarrollo de herramientas innovadoras como es el caso de las aplicaciones de Realidad Aumentada, en las cuales se combinan elementos virtuales en ambientes reales al mismo tiempo. Estas aplicaciones vienen siendo utilizadas en diferentes áreas educativas, con mayor frecuencia en temas con contenidos abstractos, con la intención de facilitar la asimilación de los mismos. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Figure 8 shows the most used keywords in the manuscripts, obtaining the 25 most relevant keywords, it is identified that augmented reality is the most mentioned by the authors, with 37%, followed by language learning with 6%, the Quechua language is observed with 5% and mobile learning with 4%. VIII, it was found that AR is a technological tool that today is available to people from a very early age [43], so that according to [42] [43] an AR application is an innovative tool when applied in a classroom, which allows us to keep the attention of students motivating them to continue learning. Similarly, [22][45]- [48] mentioned that this technology facilitates the TL process, [49]- [52] showed that AR alone would not be effective for language TL, but that the combination of traditional methodology with the application of AR results in an optimal model, in [61] they found that the interaction of 3D animations attracts the student's interest, These same in [53][54] allow the teacher to better explain the topics since the visualization of the animations enriches the conceptualization acquired by the students, an important factor that, in [63]mentioned that the teacher is an important factor as a guide of the experience.…”
Section: Manuscript Analysismentioning
confidence: 99%
“…Figure 8 shows the most used keywords in the manuscripts, obtaining the 25 most relevant keywords, it is identified that augmented reality is the most mentioned by the authors, with 37%, followed by language learning with 6%, the Quechua language is observed with 5% and mobile learning with 4%. VIII, it was found that AR is a technological tool that today is available to people from a very early age [43], so that according to [42] [43] an AR application is an innovative tool when applied in a classroom, which allows us to keep the attention of students motivating them to continue learning. Similarly, [22][45]- [48] mentioned that this technology facilitates the TL process, [49]- [52] showed that AR alone would not be effective for language TL, but that the combination of traditional methodology with the application of AR results in an optimal model, in [61] they found that the interaction of 3D animations attracts the student's interest, These same in [53][54] allow the teacher to better explain the topics since the visualization of the animations enriches the conceptualization acquired by the students, an important factor that, in [63]mentioned that the teacher is an important factor as a guide of the experience.…”
Section: Manuscript Analysismentioning
confidence: 99%